(3eNJUQ aUhU GdMce hNUhU Gdcdes - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3gPG eG ENJUQg CHh YHO Gddg eMeO Hf Ydi Hf eMeO GdYQHi GdWGFi GdMGJei GdCfOdSi ef cJGHg GdehShe HaUhU GdMce s
(3BNQgG (B:s
(3hYdjce ef fhQ YfGjJg hLYdfG ef Cgd hdGjJg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B11s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B_ (3GdHUQI (B(219 (3N(B) s
Keywords: (3GdeLGejYs